ADMINISTRATIVE AND LEGAL GROUNDS FOR THE QUALITY ASSURANCE OF HIGHER EDUCATION IN MILITARY INSTITUTIONS - Kravets, Valentyna (Honor and Law, 2023)
The article reveals the essence and content of the administrative and legal grounds for the quality assurance of higher education in military institutions through the following characteristics: the goal, which is to guarantee the capabilities of the defense forces to implement the military policy of Ukraine and participate in the NATO joint operations (combats); main directions ‒ compliance with the requirements of the quality assurance system of higher education in Ukraine and NATO quality standards; subjects of public administration: the Cabinet of Ministers of Ukraine; Ministry of Education and Science of Ukraine; National Agency for Quality Assurance of Higher Education; Ministry of Defense of Ukraine, Ministry of Internal Affairs of Ukraine (Headquarters of the National Guard of Ukraine, Administration of the State Border Service of Ukraine), Security Service of Ukraine, State Security Office of Ukraine, State Service of Special Communications and Information Protection of Ukraine; administrative and legal instruents, which consist of external quality assessment procedures common to the higher education system in Ukraine (standardization, licensing of educational activities, educational programs accreditation, institutional accreditation) and additional quality assessment procedures in higher military educational institutions (licensing of educational programs, institutional audit of professional military education); administrative and legal norms aimed at streamlining relations between subjects of public administration and military institutions on the quality assurance of higher education issues. The peculiarities of up-to-date administrative and legal instruments of the quality assurance of higher education in military institutions are determined in comparison with the external quality assessment procedures of the higher education system in Ukraine and institutional accreditation in NATO.